ВПЛИВ ТІОТРИАЗОЛІНУ ТА ГЕПАДИФУ НА МЕТАБОЛІЧНІ ПРОЦЕСИ У ТВАРИН З ГОСТРИМ ТОКСИЧНИМ ТА СУБХРОНІЧНИМ УРАЖЕННЯМ АЦЕТАМІНОФЕНОМ НА ФОНІ ДОВГОТРИВАЛОГО ЗАСТОСУВАННЯ ЕСТРОГЕНІВ ТА ПРОГЕСТИНІВ - Івануса, І. Б. (Фармацевтичний часопис, 2015)
INFLUENCE THIOTRIAZOLINE AND HEPADIF ON METABOLIC PROCESSES OF ANIMALS WITH ACUTE TOXIC AND SUBCHRONIC LESIONS BY ACETAMINOPHEN WITH PROLONGED USAGE OF ESTROGEN AND PROGESTIN I.B. Ivanusa SHEI “Ternopil State Medical University by I.Ya. Horbachevsky of MPH of Ukraine” Ethinylestradiol and levonorgestrel is widely used as oral contraceptives. Acetaminophen has more toxic activity at prolonged their usage, as indicated by our obtained results of endogenous intoxication changing. Significant changes are occurred even at seven-day acetaminophen administration in high therapeutic dose. Usage thiotriazoline and hepadif normalizes investigated parameters of metabolic processes of animals with acute toxic and subchronic lesions by acetaminophen with prolonged usage of estrogen and progestin. KEY WORDS: acetaminophen, thiotriazoline, hepadif, cytochrome oxidase, succinate dehydrogenase, microsomal oxidation. Introduction. Acetaminophen (paracetamol) is known and frequently used drug as an analgesic and antipyretic. It may be possible poisoning at usage overdoses of paracetamol. The most serious effect of acetaminophen poisoning is liver damage. Thiotriazoline is a synthetic cardio and hepatoprotector. It prevents the damage and destruction of hepatocytes. Hepadif is the most famous combined hepatoprotector. Therapeutic efficacy of Hepadyf is due to physiologically active substances of metabolic action. Therefore, we set a goal to investigate the effect of acetaminophen on the parameter of energy-saving and microsomal oxidation animals with acute toxic and subchronic lesions by acetaminophen with prolonged usage of estrogen and progestin and the correction by thiotriazoline and hepadif. INVESTIGATION METHODS. The experiments were performed on white female rats weighing 200 ±20 g, are kept on a standard diet of vivarium and free access to water. The experimental rats were divided into 4 groups, which (except 1st group) divided into two subgroups: 1st - intact (control); 2nd(a) – poisoning by acetaminophen after 40-day administration of levonorgestrel and ethinylestradiol; 2nd(b) – poisoning by acetaminophen administration within 7 days after 40-day administration of levonorgestrel and ethinylestradiol; 3rd(a) – poisoning by acetaminophen after 40-days administration of levonorgestrel, ethinylestradiol and once Thiotriazoline administration; 3rd(a) – poisoning by acetaminophen administration within 7 days after 40-days administration of levonorgestrel, ethinylestradiol and once Thiotriazoline administration; 4th(a) – poisoning by acetaminophen after 40-days administration of levonorgestrel, ethinylestradiol and Hepadyf administration; 4th(b) – poisoning by acetaminophen administration within 7 days after 40-days administration of levonorgestrel, ethinylestradiol and Hepadyf administration. RESULTS AND DISCUSSION. Cytochrome oxidase and succinate dehydrogenase activity in rat liver increase compared with affected animals at Thiotriazoline administration. Hepadyf is more effective on the energy-saving processes. Using the drugs for correction had a positive effect on the enzyme activity of microsomal oxidation. In the liver of 3rd(a) group animals N-demethylase activity increased on 29 % compared with poisoning animals, and 3rd(b) group – on 9 %. Para-hydroxylase activity at action of Thiotriazoline single administration of increased on 92 %, and the seven-time administration – parameter values was as in the control group animals. Positive influence is observed at correction by Hepadyf, but it was slightly less than at correction by Thiotriazoline. In group 4th(a) N- demethylase activity increased on 15 %, 4th(b) - on 4 %. Para-hydroxylase activity changed similarly. Erythrocytic index of intoxication at Thiotriazoline using in animals with acute poisoning by acetaminophen after 40 days administration of estrogen and progestin decreased in 1.6 times and poisoning by acetaminophen administration within 7 days - 1.7 times and approaching the level of control animals. At Hepadyf using Erythrocytic index also significantly decreased and run up to level of healthy animals in 4th(b) group. Parameter of medium weight molecules 1 (MWM1) at Thiotriazoline correction in 3rd(a) group was 45% from level of poisoning animals and approached to parameters in the control animals, in 3rd(b) group did not significantly difference from level in the control group. A similar decrease is observed at definition MWM2 – correction by Thiotriazoline normalized of this parameter. "Hepadyf" has the similar effect and to the end of the investigation period parameter was as level of control animals. Changing of cytosolic enzymes – alanine- and aspartamine-transferase activity in blood plasma of rats showed negative effect of acetaminophen on the plasma membrane of cells, accompanied by structural changes and increased permeability of membranes. Administrations of corrective drugs regulate the activity of cytoplasmic enzymes. CONCLUSIONS. As illustrated in obtained results, that parameters of oxidative processes and endogenous intoxication normalized at action of corrective drugs. So parameters of endogenous intoxication decreased and partial normalization of energy-saving and microsomal oxidation parameters.